KOMPETENSI PUSTAKAWAN PERPUSTAKAAN KHUSUS: STUDI KASUS DI PERPUSTAKAAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN - Indra Saputro, Bayu; Amir, Chaidir (BACA: Jurnal Dokumentasi dan Informasi, 2018)
Increasing competency of librarians in Kemendikbud is essential to support the vision and mission of there. Special libraries must be there professional, semi-professional, and non-professional personnel according to the National Standard of Special Library. This study examines the composition of librarians in Kemendikbud, both from the composition of position, age, and education with qualitative descriptive method. Collecting data by purposive technique. Of the respondents who manage the special library Kemendikbud as many as 136 people, only 21 people (15,44%) who occupy functional positions librarian. While the composition of expert librarians, skill librarians and administrative personal in Kemendikbud is 18:3:115. Composition of librarian age 46-50 years (28,57%), 51-55 as many as 4 people (19,05%), 56 -60 as many as 4 people (19,05%), 36-40 as many as 3 people (14,29%), 25-30 as many as 2 people (9,52%), and 41-45 as many as 2 people (9,52%). Librarians in Kemendikbud scope mostly have S1 degree as much as 15 (71,42%), S2, and D3 respectively amounted to 3 people (14,29%). Most of the librarians have educational background of the library (61,90%), education (19,05%), literature (14,29%), and state administration (4,76%).